Reconstruction of Regional Government Authority in Mining Management Post Law No. 23 of 2014: Legal Review Based on Hans Kelsen's Theory - Tiara Oktavia Namira Daud; Erman I. Rahim; Suwitno Yutye Imran (International Journal of Law, Crime and Justice, 2025)
This article examines the shift in local government authority over mineral and coal mining management following the enactment of Law Number 23 of 2014 on Regional Government. The transfer of authority from regency/city governments to provincial and central governments has created normative disharmony between the Regional Government Law and the Mining Law, resulting in legal uncertainty at the implementation level. Using a normative juridical approach and Hans Kelsen’s theory of the hierarchy of norms, this article analyzes the legal validity of the transfer and identifies structural conflicts within the legal system. The findings indicate that the current regulation lacks both hierarchical consistency and functional clarity. Therefore, a reconstruction of the legal framework for mining governance is required to balance the principle of legality with the concept of regional autonomy. A model of limited delegation, sectoral regulatory harmonization, and the application of multilevel governance are proposed as key recommendations to ensure a fair, effective, and constitutional relationship between central and local governments.